FEMINISME PEREMPUAN PESANTREN: HEGEMONI DAN RELASI KUASA - Faizi, Ahmad (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: This study aims to uncover the feminism of pesantren women. The source of the data in this research is the linguistic data in the novel Perempuan Berkalung Sorban by Abidah El-Kholieqy. The data is collected by listening and note method which is then analyzed using the theory of feminism and hegemony. The results of this study indicate that there has been a hegemony in the pesantren education environment, in the family environment, and in the community environment. Hegemony comes from men and women themselves.